Preliminary investigation of Mitragyna speciosa (Korth.) Havil leaves methanol crude extract and formulation towards wound healing property - Zakaria, Fazila (2023)
The demand for natural-based remedies is rising due to their safety and efficiency compared to synthetic-based medicine. In view of this, the unique bioactive properties of Mitragyna speciosa (Korth.) Havil (MS) have attracted high interest for its potential application in the pharmacological industry. This study aimed to determine in vitro the wound healing capacities of methanol crude extract (MCE) and fractions of MS leaves in promoting proliferation, monolayer migration, and angiogenesis activities. The ultrasound-assisted extraction (UAE) method using response surface methodology (RSM) was used to optimised the production of MCE. The optimised extraction conditions were then used to obtain the MCE and the corresponding fractions (hexane, dichloromethane, ethyl acetate, and butanol) using the liquid-liquid extraction (LLE). The developed quadratic polynomial model correlated with the experimental data is based on the coefficient of determination (R2) of the extraction yield (0.9972, p < 0.0001) and the total phenolic content (TPC) (0.9553, p < 0.0001). At 25 ˚C, 15 min sonication time, and 10 mL/g of solvent to solid ratio, the optimal conditions recorded an extraction yield and TPC of 21.99 % and 144.70 (mgGAE)/g, respectively. The wound healing screening of the MCE and fractions revealed that the semi polar solvent of the ethyl acetate fraction (EAF) exhibited highest TPC (277.55 ± 4.89 mg GAE/g) and total flavonoid content (TFC) (90.72 ± 8.96 mg RE/g), a strong antioxidant of DPPH IC50 (25.24 ± 30.56 μg/mL), strong antibacterial activity against Staphylococcus aureus (17.89 ± 0.68 mm), and moderate anti-inflammatory inhibition (42.36 ± 1.53 %). The EAF showed the highest migration rate and branching length at a lower concentration (3.13 μg/mL) of 70.85 % and 9014.33 pixels, respectively. EAF was selected to encapsulated into the newly developed cubosomes formulations using a single stabiliser of F127 (F) and a combined stabiliser of F127 and Tween 80 (Mix FT). The optimal composition of formulation F consisted of 0.5 % F127 as it exhibited the lowest particle size (PS) of 177.93 ± 0.65 nm. Meanwhile the formulation Mix F-T consists of 0.25 % F127 and 0.25 % Tween 80 as it demonstrated lowest PS (141.53 ± 0.21 nm). The measured PDI was 0.17 ± 0.01(F) and 0.23 ± 0.01 (Mix F-T), zeta potential was - 26.40 ± 0.10 (F) and – 28.07 ± 2.40 mV (Mix F-T), and the pH was 4.17 (F) ± 0.02 and 4.18 ± 0.03 (Mix F-T). Furthermore, % entrapment efficiency was 95.63 ± 1.54 % (F) and 90.09 ± 1.89 % (Mix F-T). Both formulations showed no toxic effect on the 3T3 fibroblast cells, with cell viability values of higher than 80 % (up to 500 μg/mL). The mortality rate of zebrafish embryos was unaffected when exposed to all formulations of less than 500 μg/mL. Normal morphological features were observed when zebrafish embryos were exposed to unencapsulated EAF at concentrations less than 200 μg/mL, except that they exhibited hatching inhibition compared to the control group. This study suggests the potential of MS as wound healing and thus supporting its traditional claim.